Práticas de socialização parental e comportamentos agressivos de crianças com transtorno do espectro autista - Carvalho, Mírian Carla Lima (2023)
This dissertation was structured in four chapters. In the first chapter, a non-systematized review was presented, explaining the following themes: socialization practices, aggression and the characteristics of Autistic Spectrum Disorder (ASD). In the second chapter, a review was carried out, whose general objective was to systematically evaluate the bibliographical production, over the last 20 years, on the relationship between parental socialization and aggressive behavior in children with Autistic Spectrum Disorder. The inclusion criteria of the articles were: publications from the last 20 years, within the chosen theme and with children diagnosed with ASD as a sample. The exclusion criteria used were: theses, dissertations and duplicate articles. From the search carried out, 25 articles were considered for the discussion of the data. In general, it was found that aggressive behaviors cannot be considered specific symptoms that characterize ASD, but may be associated with other factors related to ASD, such as communication deficits, sensory deficits, behavioral patterns and the presence of other comorbidities. It was also possible to notice that parents of people with ASD tend to use excessive protection and control practices; specifically regarding the maternal practices of children with ASD, some research has shown that they made little use of Rules and Discipline and used more Positive Parenting. In addition, it was found that aggressive behaviors were positively correlated with Discipline and Harsh Punishment, as well as it was found that parenting styles were positively and statistically significantly related to aggressive behaviors.In the third chapter, the general objective was to find out to what extent the socialization practices adopted by mothers of children with Autistic Spectrum Disorder and mothers who had typically developing children were related to their perception of aggressive behavior in children. your children. For this study, the following hypotheses were elaborated: (a¹) The use of external control by mothers of children with ASD positively predicts the mothers' perception of aggressive behavior (physical aggression, anger and hostility) attributed to their children; (a²) The use of internal control by mothers of children with ASD negatively predicts aggressive behavior (physical aggression, anger and hostility) attributed to their children; (b¹) Mothers of children with ASD at mild and moderate levels of support use more internal control practices than mothers of children with severe ASD; (b²) Mothers of children with a severe level of support use more external control practices than mothers of children with mild and moderate ASD levels; (c¹) Mothers perceive their sons with ASD to be more physically aggressive than their daughters with ASD; (c²) Mothers perceive their sons with ASD to be angrier than their daughters with ASD; (c³) Mothers perceive their sons with ASD with more hostility than their daughters with ASD; (d¹) Mothers of children with Autism Spectrum Disorder perceive more anger in their children than mothers with typically developing children; (d¹) Mothers of children with Autism Spectrum Disorder perceive more anger in their children than mothers with typically developing children; (d²) Mothers of children with Autism Spectrum Disorder perceive more physical aggression in their children than mothers with typically developing children; (d³) Mothers of children with Autism Spectrum Disorder perceive more hostility in their children than mothers with typically developing children; (d4) Mothers of typically developing children perceive more verbal aggression in their children than mothers of children with Autistic Spectrum Disorder. (e¹) Mothers of children with TD will make more use of internal control than mothers of children with ASD. Ninety mothers of children diagnosed with Autistic Spectrum Disorder (ASD) were interviewed. The mothers were aged between 26 and 66 years (M= 37.10; SD=7.54) and the children, diagnosed with ASD, were aged between 8 and 10 years and 11 months (M= 8 .93; SD=0.79), with 80% (f = 72) male and 20% (f = 18) female. Also, there were 46 mothers of typically developing children, aged between 22 and 49 years (M = 33.80; SD=5.74); the children were aged between 7 and 10 years (M = 8.28; SD = 1.10), 19 (41.3%) males and 27 (58.7%) females. For data collection, the following were used: a sociodemographic questionnaire, the Aggression Questionnaire – BPAQ Adapted version for mothers and the Socialization Techniques Instrument. In general, the statistically significant data were that: the mothers' perception of external control was able to predict the perception of physical aggression and anger in children with ASD; mothers with children with a more severe level of ASD made little use of explanations and those with mild or moderate children made more use of explanations; and girls with ASD showed more anger and hostility than boys with ASD: when comparing the perception of mothers of children with ASD with mothers of children with TD, it was possible to notice that mothers of children with ASD perceived more anger in their children than mothers of children with TD; and, when compared regarding the perception of the use of practices, mothers of children with ASD made less use of internal control than mothers of children with TD. Finally, in the fourth chapter, a general discussion was carried out, based on the empirical studies already carried out.